Review: Improving the therapeutic index of 8-aminoquinolines by the use of drug combinations: review of the literature and proposal for future investigations. - Myint, H; Berman, J; Walker, L; Pybus, B; Melendez, V; Baird, J; Ohrt, C (2011)
Because 8-aminoquinolines affect critical survival stages of Plasmodium parasites, treatment and control of malaria could be markedly improved by more widespread use of these drugs; however, hemolytic toxicity, which is widely prevalent in G6PD-deficient patients, severely constrains this use. Primaquine was approved more than 50 years ago after extensive clinical testing. Review of the mid-20th century literature in the light of present understanding of pharmacokinetics and metabolism suggests that manipulation of these factors might dissociate 8-aminoquinoline efficacy from toxicity and lead to an improved therapeutic index.